Dialogue - Ramsey, Jean; White, Judith; Lam, Danny; Boozer, Bob; Boettger, Rick (Academy of Management Review, 1993)
Several letters to the editor are presented in response to earlier issues' articles. They include the “Theory Development Forum,” “Thanks and some suggestions for further special issues,” and “Postmodernism and spiritual impoverishment.”